2021
DOI: 10.1186/s12933-021-01295-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of estimated fluid volumes following initiation of empagliflozin in patients with type 2 diabetes and cardiovascular disease: a secondary analysis of the placebo-controlled, randomized EMBLEM trial

Abstract: Backgrounds/Aim Sodium glucose co-transporter 2 inhibitors promote osmotic/natriuretic diuresis and reduce excess fluid volume, and this improves cardiovascular outcomes, including hospitalization for heart failure. We sought to assess the effect of empagliflozin on estimated fluid volumes in patients with type 2 diabetes and cardiovascular disease (CVD). Methods The study was a post-hoc analysis of the EMBLEM trial (UMIN000024502), an investigator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…In this regard, changes in some fluid volume parameters indicative of a hemodynamic effect of SGLT2 inhibition are likely to be associated with clinical benefits [ 34 , 36 ]. Recent studies have reported a consistent reduction in ePV status in patients with HFrEF, regardless of their diabetes status, [ 20 ] and also in patients with T2D and cardiovascular diseases, regardless of their background clinical characteristics and medications [ 37 ]. The present study showed that the effect of canagliflozin treatment on ePV reduction was also consistent across the baseline use of glucose-lowering agents.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, changes in some fluid volume parameters indicative of a hemodynamic effect of SGLT2 inhibition are likely to be associated with clinical benefits [ 34 , 36 ]. Recent studies have reported a consistent reduction in ePV status in patients with HFrEF, regardless of their diabetes status, [ 20 ] and also in patients with T2D and cardiovascular diseases, regardless of their background clinical characteristics and medications [ 37 ]. The present study showed that the effect of canagliflozin treatment on ePV reduction was also consistent across the baseline use of glucose-lowering agents.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest explanation for such fast and short-term effects of empagliflozin in HFpEF is its diuretic effect [43]. However, the diuretic effect of empagliflozin is different from loop diuretics in that empagliflozin caused a significant increase in 24-hour urine volume without an increase in urinary sodium and electrolyte-free water clearance [44] and a significant decrease in estimated plasma volume calculated by the Straus formula and estimated the extracellular volume determined by the body surface area [45]. A pooled analysis of both the EMPEROR-Reduced and EMPEROR-Preserved trials indicated that the magnitude of the effect of empagliflozin on HF outcomes and health status was similar in patients with ejection fractions < 25% to < 65%, but it was attenuated in patients with an ejection fraction ≥ 65% [46], which may herald the recognition of a new phenotype characterized by supra-normal left ventricular ejection fraction [47].…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 Other studies have also reported that SGLT2 inhibitors reduced the ePV in patients with T2DM complicated by cardiovascular diseases or HFrEF. 20 , 21 In addition, SGLT2 inhibitors reduced pulmonary arterial pressure in patients with heart failure. 26 These results support that SGLT2 inhibitors can reduce intracellular volume by diuretic effects related to both glycosuria and natriuresis, consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Recently, SGLT2 inhibitors have been reported to reduce estimated plasma volume (ePV). 18 , 19 , 20 , 21 Although these results suggest that SGLT2 inhibitors may be effective in reducing intravascular volume, which may improve heart failure prognosis, there is little evidence of the efficacy of SGLT2 inhibitors on intravascular volume in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%